CHATGPT DAN DAMPAKNYA BAGI PEMBELAJARAN PAI - Ubaidillah Fadli Achmad; Hamam Burhanuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study seeks to examine the influence of ChatGPT on students’ comprehension levels in Islamic Religious Education (PAI), analyze its strengths and limitations within instructional settings, and formulate strategic recommendations for its optimal integration into Islamic education. The research employs a literature review approach by systematically analyzing scholarly publications indexed in Google Scholar. The review process focuses on evaluating, synthesizing, and interpreting prior findings related to the implementation of ChatGPT in Islamic education contexts.The findings indicate that ChatGPT contributes positively to PAI learning by fostering interactive engagement, increasing learning flexibility, and enabling adaptive instructional content tailored to individual learner needs. Nevertheless, ethical considerations such as information reliability, doctrinal accuracy, and excessive technological dependency remain significant concerns. This study contributes to the academic discourse by highlighting the transformative potential of artificial intelligence in enhancing Islamic education quality while emphasizing the necessity of ethical supervision. Therefore, the integration of ChatGPT in PAI must be accompanied by structured monitoring to ensure the credibility, relevance, and theological alignment of the information delivered.